1989
DOI: 10.1007/bf02554181
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative adaptation of the small intestine after total colectomy and J-pouch-anal anastomosis

Abstract: Twelve patients who underwent total colectomy and J-pouch-anal anastomosis were followed up to 3 years after surgery to evaluate the functional and morphologic changes of the small-bowel reservoir. Intestinal absorption was impaired for lactose in 18 percent, for D-xylose in 27 percent, and for 75SeHCAT in 83 percent. Morphologic changes in ileal-pouch specimens consisted of a marked flattening of the villi and augmentation in crypt number and length. The number of Paneth's cells was increased compared with no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
2
3

Year Published

1992
1992
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(34 citation statements)
references
References 20 publications
0
29
2
3
Order By: Relevance
“…Retention of 75Se-taurohomocholate (SeHCAT) is decreased in these patients compared to non-operated colitis patients (75) or healthy controls (76,77). Postprandial conjugated bile acid levels increase to a lower extent in ileal pouch patients compared to healthy subjects (78).…”
Section: Bile Acid Metabolismmentioning
confidence: 96%
See 1 more Smart Citation
“…Retention of 75Se-taurohomocholate (SeHCAT) is decreased in these patients compared to non-operated colitis patients (75) or healthy controls (76,77). Postprandial conjugated bile acid levels increase to a lower extent in ileal pouch patients compared to healthy subjects (78).…”
Section: Bile Acid Metabolismmentioning
confidence: 96%
“…Impaired intestinal absorption of D-xylose and low serum iron levels have been reported in ileal pouch patients. Nevertheless, clinical signs of malnutrition or malabsorption are rare in these patients (77). Low vitamin B12 levels and decreased Schilling tests have been found in patients with ileal pouch-anal anastomosis (57,74,82).…”
Section: Malabsorptionmentioning
confidence: 99%
“…Several studies have shown that the ileal pouch mucosa undergoes morphological changes and that most probably it reflects an adaptive response to the new luminal environment [4,5,6]. Transformation to a glandular morphology resembling colonic mucosa is common [7].…”
Section: Discussionmentioning
confidence: 99%
“…Histochemical changes in pouch mucin from sialo to sulphomucin are seen in pouches with villous atrophy [5]. These findings have led to the hypothesis that the pouch mucosa undergoes colonic metaplasia as an adaptive change but it may become vulnerable to immune damage or polyp formation, which eventually affects colonic and not ileal mucosa in the susceptible population [5,6]. Many studies until now state that the great majority of functioning ileal reservoirs develop chronic inflammation and villous abnormality regardless of the initial indication for pouch surgery [1,5] as also found in our study (Fig 1 refers).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies regarding the effect of proctocolectomy on bile acid metabolism were controversial. Several studies indicated that intestinal absorption of bile acids is impaired after proctocolectomy and IPAA [7,8,21,22,23]. It was assumed that impaired intestinal bile acid absorption was followed by formation of a more lithogenic bile and an increased incidence of cholelithiasis [5,6].…”
Section: Discussionmentioning
confidence: 99%